Articulate cartilage of humeral bone structure characteristics under high temperature - O. S. Laorukooa; L. A. Aleksina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2014)
Articulate cartilage of the humeral bone head structure characteristics according to the temperature data and prolongation of their action under high temperature (50 - 90 °С) are demonstrated on the basis of anatomy and histology studies. In female morphological changes occurred much earlier than in male due to less thickness of their articulate cartilage. The obtained findings of high temperature damage effects on the cartilage can be explained by cell protein denaturation in temperature rising even more than +45 °C. More frequent occurence of musculoskeletal system diseaes in metallurgists is explained by the results obtained.